Enid Blyton's Claudine at St Clare's - "Blylon, Enid" (Mammoth: London, 1996)
St. Clare's boarding-school has some interesting newcomers. Claudine, a French girl, causes great excitement by doing and saying exactly what she likes, and Eileen's mother is the new Matron.
Keywords: Children's stories